THERAPEUTIC JURISPRUDENCE AND LINGUISTIC RIGHTS: BEYOND ACCESS TO CARE - Léger-Riopel, Nicholas (Comparative Legilinguistics, 2020)
Therapeutic jurisprudence is an interdisciplinary examination on the effect of the law on the mental and emotional health of those implicated in the judicial process. It concentrates primarily on the psychological impact of legal rules and procedures, as well as on the behaviour of legal players. TJ is a tool not often used in the promotion of linguistic rights. Endowed with a double mission, both normative and descriptive, TJ makes it possible to measure the impact of health incidences. In providing legal reformers with more precise tools to assess the health impacts of new linguistic rights standards TJ offers such a path of implementation of linguistic rights – not only from the formal point of view, but by keeping in mind their actual effectiveness - integrating law and languages in a way to mitigate their consequences on a population’s health.